Penyisihan Minyak dalam Emulsi Air Bilga Menggunakan Proses Elektrokoagulasi - Soeprijanto Soeprijanto; Lily Pudjiastuti; R.O. Saut Gurning (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
Electrocoagulation is electrochemical water treatment and the simplest technology for wastewater treatment using an electrochemical cell in which the supply of DC power is applied to the electrodes made of aluminum, and the electrolyte is wastewater. The experiments were conducted using oily bilge water in an electrocoagulation batch reactor. The electrodes were aluminum with dimensions (20 cm × 8 cm × 0.2 cm) mounted at a distance of 4 cm vertically. Aluminum plate was then connected to a direct current power supply having a 220 V input and output of 10 V with electric current of 10-15 A. The total area of the effective working of the plate was 160 cm2 when was immersed at a depth of 10 cm to the solution. The deposition process was maintained constant around 30-60 minutes. The results showed that the process could reduce the turbidity from114.1 to14.3 NTU and the highest solids concentration obtained was 12.54 g/l with initial oil concentration of 50 g/l within 60 minutes. The largest oil removal of 98.75% was obtained using the initial concentration of oil 75 g/l and the lowest of 96.25% was obtained with the initial oil concentration of 150 g / l.